2021
DOI: 10.1007/s00203-021-02245-2
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide (NO) elicits aminoglycoside tolerance in Escherichia coli but antibiotic resistance gene carriage and NO sensitivity have not co-evolved

Abstract: The spread of multidrug-resistance in Gram-negative bacterial pathogens presents a major clinical challenge, and new approaches are required to combat these organisms. Nitric oxide (NO) is a well-known antimicrobial that is produced by the immune system in response to infection, and numerous studies have demonstrated that NO is a respiratory inhibitor with both bacteriostatic and bactericidal properties. However, given that loss of aerobic respiratory complexes is known to diminish antibiotic efficacy, it was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…2 B). Since the respiratory inhibitor and NO-donor GSNO has previously been shown to diminish gentamicin lethality (Ribeiro et al 2021 ), it was of interest to investigate the hypothesis that exposure to GSNO could dissipate the PMF. This was tested under the conditions used in this previous study, and a significant dissipation of the membrane electrical potential was observed in response to GSNO (Supplemental Data, Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2 B). Since the respiratory inhibitor and NO-donor GSNO has previously been shown to diminish gentamicin lethality (Ribeiro et al 2021 ), it was of interest to investigate the hypothesis that exposure to GSNO could dissipate the PMF. This was tested under the conditions used in this previous study, and a significant dissipation of the membrane electrical potential was observed in response to GSNO (Supplemental Data, Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A clear increase in fluorescence is observed of approximately twofold between cells exposed to DNP and those not exposed to DNP. Since the NO-donor GSNO, a respiratory inhibitor, has previously been shown to provide resistance to gentamicin in the pathogenic E. coli EC958 ST131 strain (Ribeiro et al 2021), it was also of interest to confirm that GSNO can dissipate the PMF, which indeed it can (Supplemental data, Fig. S2).…”
Section: Dissipation Of the Proton Motive Force Diminshes Gentamicin Lethality In Aerobially-grown Cellsmentioning
confidence: 98%
See 1 more Smart Citation
“…These results indicate that both reprogramming metabolite Ala and antibiotic Gent play a role in the reprogrammed metabolome. NO-mediated resistance to aminoglycosides is not reported in V. alginolyticus , but NO protects other bacteria including Gram-negative Escherichia coli, Salmonella enterica , and Pseudomonas aeruginosa and the Gram-positive Staphylococcus aureus from killing mediated by aminoglycosides [ 33 , 34 ]. This is because blockage of aerobic respiration by high NO fluxes reduces drug uptake, thereby promoting aminoglycoside resistance [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…A line of evidence has indicated that NO level is related to bacterial sensitivity or resistance to antibiotics [ 39 , 40 ]. The finding on the role of NO in impacting Gent-mediated killing is not new [ 34 ], but the NO decrease in this case is attributed to the synergy of Ala and Gent and this plays a role are novel.…”
Section: Discussionmentioning
confidence: 99%